Comprehensive investigation of core-shell dimer nanoparticles size, distance and thicknesses on performance of a hybrid organic-inorganic halide perovskite solar cell. (28th March 2018) - Heidarzadeh, Hamid
Abstract: Significant performance enhancement in an ultrathin perovskite (CH3 NH3 PbI3 ) solar cell is done using plasmonic embedded core–shell dimer nanoparticles. Three-dimensional finite difference time-domain (FDTD) method is used. A perovskite absorber with a volume of 400 × 400 × 200 nm 3 is considered. At first, a cell with one embedded nanoparticle is simulated. Absorptance of CH3 NH3 PbI3 absorber and gold nanoparticle are obtained. An optimization is done. Then a cell with embedded dimer nanoparticles is evaluated. The results show higher photocurrent enhancement for that in compared to a cell with one embedded nanoparticle. To further photocurrent enhancement, gold-SiO2 core–shell nanoparticles are used. Photocurrents of 23.37 mA cm −2, 23.3 mA cm −2, 22.5 mA cm −2 and 21.47 mA cm −2 are obtained for a cell with two embedded core–shell nanoparticles with core radius of 60 nm and shell thickness of 2 nm, 5 nm, 10 nm and 20 nm, respectively. It is important to mention that the photocurrent is 17.9 mA cm −2 for reference cell and 19.8 mA cm −2 for a cell with one embedded nanoparticle. Higher photocurrent is due to the near-field plasmonic effect.